Strengthening Integrated Health Center Service for the Elderly through Cadre Training and Mentoring - Saidah Rauf; Rigoan Malawat (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2022)
Posyandu for the elderly is a community-driven and agreed-upon integrated service station for the elderly in a specific location where they can receive health care. Currently, not all provinces in Indonesia (43.9%), including Maluku, hold Posyandu for the elderly. The Mosso Villages in Central Maluku Regency's Tehoru District has never offered posyandu services to the elderly. The absence of skilled cadres, infrastructure, and a small number of health workers causes posyandu's lack of action in this area. This community engagement aimed to strengthen the elderly posyandu in Mosso village by providing cadre training and mentoring. Ten cadres have been trained, and their knowledge and abilities have improved due to the training. The mentoring activities revealed that the Posyandu Wae BaK and Wae Lisa provided routine services every month and that the cadres could provide posyandu services for the elderly on their own.